2016
DOI: 10.19080/ajpn.2016.01.555561
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Diagnosis, and Current Practices in the Management of Intraventricular Hemorrhage in Preterm Infants: A Review

Abstract: Intraventricular hemorrhage (IVH) is one of the major complications in premature infants, and its management is quite challenging. This review article describes the pathophysiology, risk factors, and complications of IVH. Further, it explains the current diagnosis and treatment of IVH, along with the recent advances in its management. IVH can occur due to fragility of germinal matrix vasculature, impairment of cerebral auto-regulation, coagulation disorders, genetic factors, and oxygen toxicity. Cranial ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
2
11
0
4
Order By: Relevance
“…IVH is one of the major complications in premature infants, and an appropriate predictor of neuro-developmental outcomes in very low birth weight neonates. [ 15 16 ] The ratio of IVH in the present study was 8.7%. IVH grades 1, 2, 3, and 4 were found in 38.3%, 33.1%, 14.3%, and 14.3% of cases, respectively.…”
Section: Discussionsupporting
confidence: 42%
“…IVH is one of the major complications in premature infants, and an appropriate predictor of neuro-developmental outcomes in very low birth weight neonates. [ 15 16 ] The ratio of IVH in the present study was 8.7%. IVH grades 1, 2, 3, and 4 were found in 38.3%, 33.1%, 14.3%, and 14.3% of cases, respectively.…”
Section: Discussionsupporting
confidence: 42%
“…In UAE, the rate of combined severe IVH and PVL among VLBW infants was found to be 8% [ 8 ]. Globally, the rates of severe IVH and PVL are decreasing since introduction of antenatal steroids, better resuscitation at birth, and more judicious use of ventilatory support [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the patients in NEC group were prone to develop PDA and IVH, even though the proportion of preterm births was similar between the NEC group and matched controls. PDA, hypoxia, and hypotension have been identified as risk factors for NEC and IVH (25,26), and these factors are commonly responsible for circulatory instability or ischemic and hypoxic injury. IVH is considered to be a predictor of neurodevelopmental outcomes in preterm infants (27).…”
Section: Discussionmentioning
confidence: 99%